1998
DOI: 10.1053/euhj.1998.1095
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a nurse-monitored, outpatient-care programme for elderly patients with moderate-to-severe, chronic heart failure

Abstract: Given the selection criteria and the outline of the interventions, the outpatient, nurse-monitored, symptom-management programme was not feasible for the majority of these elderly patients with moderate-to-severe, chronic heart failure, mainly because of the small proportion of eligible patients and the high drop-out rate. Management of these patients would have to be more adjusted to their home situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
0
10

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(127 citation statements)
references
References 16 publications
5
112
0
10
Order By: Relevance
“…Five studies reported that less than 50% of patients were at target doses [29,30,[33][34][35]. In the study by McDonald et al over 50% of enrollees received target doses of ACEIs [31,32]. This study also reported significant reductions in the primary outcomes we evaluated and the overall results favored intervention patients.…”
Section: Sourcementioning
confidence: 60%
See 3 more Smart Citations
“…Five studies reported that less than 50% of patients were at target doses [29,30,[33][34][35]. In the study by McDonald et al over 50% of enrollees received target doses of ACEIs [31,32]. This study also reported significant reductions in the primary outcomes we evaluated and the overall results favored intervention patients.…”
Section: Sourcementioning
confidence: 60%
“…Cline et al [30] Ekman et al [31] McDonald et al [32]; Ledwidge et al [33] Doughty et al [34] Kasper et al [35] Stromberg et al [36] Discharge planning specifically or consistently defined. The median Jadad score was 3.5 (IQR 3-4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Replicating these multi-disciplinary interventions in routine practice is challenging, as many elderly patients are not able to attend frequent clinic visits, there are a limited number of specialist nurses, and a limit on the number of patients with whom they can maintain frequent contact. 7 Importantly, in the UK only 20% of heart failure patients discharged from hospital have any form of specialist follow-up. 8 Telehealth has the potential to deliver specialist services closer to patients' homes.…”
Section: Introductionmentioning
confidence: 99%